Clinical and laboratory aspects of the Aspirin-like defect as hereditary thrombocytopathy - Rolf, N.; Bugert, P.; Gehrisch, S.; Siegert, G.; Suttorp, M.; Knöfler, R. (Hämostaseologie, 2009)
The Aspirin-like defect (ALD) is caused by defects in the intraplatelet arachidonic acid (AA)-metabolism. We here present the characteristics of a larger cohort in a single centre. Patients, methods: Based on 17 ALD index patients bleeding symptoms, agonist-induced platelet aggregation and closure times in the PFA-100® test were analysed in a family cohort of altogether 52 individuals from 17 families. Absent aggregation to AA (maximal aggregation ≤10%) was the main diagnostic criterion. A mild ALD was diagnosed when aggregation was 11–40%. Results: In addition to 17 ALD index patients, 13 family members displayed ALD. 4 family members were diagnosed with a mild ALD. Epistaxis, easy bruising, menorrhagia and perioperative hemorrhage were the most common bleeding symptoms, whereas three quarters of ALD patients presented with ≥ 1 bleeding symptoms. Conclusion: In case of a bleeding tendency diagnostic procedures should rule out primary haemostatic defects. Hereditary platelet function defects including ALD are an important differential diagnosis. Family studies are reasonable.
Keywords: Aspirin-like defect; inherited platelet function disorder; children